Origin of photoluminescence around 2.6–2.9 eV in silicon oxynitride - Noma, Takashi; Seol, Kwang Soo; Kato, Hiromitsu; Fujimaki, Makoto; Ohki, Yoshimichi (Applied Physics Letters, 2001)
A broad photoluminescence (PL) around 2.6–2.9 eV is known to appear in hydrogenated silicon oxynitride. Although its origin was reported to be Si–N bonds, it is not so clear since the material contains hydrogen. In the present research, we have confirmed that the same PL appears in silicon oxynitride grown by nitriding of silicon dioxide. The depth profile of the PL intensity agrees with that of the nitrogen concentration. Furthermore, the emission spectrum, excitation spectrum, and decay constant of this PL agree with those of the PL observed in silicon nitride. Based on these results and theoretical discussion, the origin of the 2.6–2.9 eV PL is estimated to be Si–N bonds.